imX experience partners discuss manufacturing trends.
Methods Machine Tools Inc. (Sudbury, MA) and Kennametal Inc. (Latrobe, PA) will be among the eight Experience Partners at the imX-Interactive Manufacturing Experience event to be held in Las Vegas, September 12-14. Byron Deysher, president and CEO, Methods Machine Tools and John Tucker, vice president and President Business Groups, Kennametal Inc., recently discussed with Manufacturing Engineering the future of manufacturing in the US and conditions in the machine tool market.